2023
DOI: 10.1155/2023/8598585
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical Properties for Epoxy Resin in Nano Composite Diffusion

Abstract: This research work developed a method for the analysis of epoxy matrix nanocomposites used in epoxy resin with the incorporation of Al2O3 and SiO2 nanoparticles. The different tests were performed in order to derive the mechanical characteristics and wear properties of Al2O3 and SiO2 nanoparticles. The mixing is performed using an ultrasound process where the nanoparticles are mixed with the resin for a homogeneous diffusion. The strengths observed for the nanocomposite were higher for bending and impact stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A critical review of literature suggests that glass fiber reinforcements provide good stiffness and high tensile strength 6 . Few studies also reported that Epoxy polymer matrix provides good stiffness, high strength and good corrosion resistance 7,8 . The filler material, weight ratio of resin to fiber and the particle size of the fillers influence the mechanical performance of the polymer composites [9][10][11] .…”
mentioning
confidence: 99%
“…A critical review of literature suggests that glass fiber reinforcements provide good stiffness and high tensile strength 6 . Few studies also reported that Epoxy polymer matrix provides good stiffness, high strength and good corrosion resistance 7,8 . The filler material, weight ratio of resin to fiber and the particle size of the fillers influence the mechanical performance of the polymer composites [9][10][11] .…”
mentioning
confidence: 99%